Materials Development for Teaching English using Quizizz to the 10th Graders of Modeling Design and Building Information Department in Vocational High School 3 Mataram - Reviana, Isabela Putri; Sujana, I Made; Saputra, Agus; Apgrianto, Kurniawan (Jurnal Ilmiah Profesi Pendidikan, 2024)
General English is not considered adequate for vocational students. They need a curriculum built around "English for Specific Purposes" (ESP) to develop the targeted language skills required for their chosen field especially in Modeling Design and Building Information Department. This study examines the development of ESP-Based English material using Quizizz for vocational schools, along with student opinions on the material with Quizizz. Using R&D (Research and Development) methodology with ADDIE model, the study progressed through data collection, analyzing data, designing new materials, expert validation, developing the materials, implementing the ESP-based English material using Quizizz, and giving the final questionnaire students to find out student’s opinions. The research involved 30 participants who were X DPIB A at SMKN 3 Mataram. The data were analyzed qualitatively and quantitatively. The result of this research are; 1) The design of ESP-Based English material is developed into 4 distinc thematic topics (The introduction of the material, Professional Profiles, Object Identification, and Describing Places) by inserting vocabulary appropriate to the major and the materials were delivered to students via the interactive learning platform Quizizz. Interactive features such as; multiple choice, fill-in-the-blanks, polls, picture-matching, open-ended questions, and drag-and-drop activities enriched the exercise design. 2) The total score of 79.083% in the student’s opinions questionnaire suggests that students are highly interested and engaged with the English ESP materials developed using Quizizz.